2006
DOI: 10.4000/etudesafricaines.6198
|View full text |Cite
|
Sign up to set email alerts
|

Pactes, alliances et plaisanteries

Abstract: Ce document a été généré automatiquement le 19 avril 2019. © Cahiers d'Études africaines 10 Le concept de « parenté à plaisanterie » ou « joking relationship » 14 a donc une historicité qu'il faut mettre en évidence. Des pratiques ont bel et bien été décrites, lesquelles ont été nommées par les acteurs en situation et subsumées par les « passeurs » et les ethnologues dans la catégorie générale des « parentés à plaisanterie ». Des prototypes fameux, comme la relation Peuls/forgerons (Doumbia 1936) ou Dogon/Bozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Although we focused on the role of registration cost in deriving our result, the transition towards a full registration system could be accelerated by cultural change and the weakening of the norms governing kinship relationships (Canut and Smith 2006). Finally, our hybrid model showed that when registration costs are high, allowing households to transact informally along trusted relationships leads to a greater economic surplus.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although we focused on the role of registration cost in deriving our result, the transition towards a full registration system could be accelerated by cultural change and the weakening of the norms governing kinship relationships (Canut and Smith 2006). Finally, our hybrid model showed that when registration costs are high, allowing households to transact informally along trusted relationships leads to a greater economic surplus.…”
Section: Discussionmentioning
confidence: 86%
“…Proposition 1: There is a single stable equilibrium, in which all landowners between the city center and the city fringe 12 Proof: See Appendix A.…”
Section: The Competitive Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…The social ‘culture of consensus’ and joking relationships, e.g. a set of institutionalised jokes and obligations between particular groups common in West Africa (Canut & Smith 2006) was believed to guarantee peace between Mali's different communities. Despite its persistently low levels of electoral participation (from 23% to 43% between 1992 and 2007), Mali provided stability in an otherwise chaotic or politically gridlocked region (civil war in Côte d'Ivoire, failed democratic transition in Togo, authoritarian rule in Burkina Faso, repeated coups in Guinea and Mauritania).…”
Section: How Donors Have Perpetuated a Fiction Disconnected From Popumentioning
confidence: 99%
“…Informal rules and hierarchies between officials are partially based on joking relationships, e.g. a set of institutionalized jokes and social obligations between particular groups common in West Africa (Canut and Smith 2006). Some interns with no clear formal status work at the unit; they survive on solidarity and redistribution or await permanent positions.…”
Section: Technical Assistance Beyond Mythsmentioning
confidence: 99%